Cerebral lactate dynamics across sleep/wake cycles - Rempe, Michael J.; Wisor, Jonathan P. (Frontiers in Computational Neuroscience, 2015)
Cerebral metabolism varies dramatically as a function of sleep state. Brain concentration of lactate, the end product of glucose utilization via glycolysis, varies as a function of sleep state, and like slow wave activity (SWA) in the electroencephalogram (EEG), increases as a function of time spent awake or in rapid eye movement sleep and declines as a function of time spent in slow wave sleep (SWS). We sought to determine whether lactate concentration exhibits homeostatic dynamics akin to those of SWA in SWS. Lactate concentration in the cerebral cortex was measured by indwelling enzymatic biosensors. A set of equations based conceptually on Process S (previously used to quantify the homeostatic dynamics of SWA) was used to predict the sleep/wake state-dependent dynamics of lactate concentration in the cerebral cortex. Additionally, we applied an iterative parameter space-restricting algorithm (the Nelder-Mead method) to reduce computational time to find the optimal values of the free parameters. Compared to an exhaustive search, this algorithm reduced the computation time required by orders of magnitude. We show that state-dependent lactate concentration dynamics can be described by a homeostatic model, but that the optimal time constants for describing lactate dynamics are much smaller than those of SWA. This disconnect between lactate dynamics and SWA dynamics does not support the concept that lactate concentration is a biochemical mediator of sleep homeostasis. However, lactate synthesis in the cerebral cortex may nonetheless be informative with regard to sleep function, since the impact of glycolysis on sleep slow wave regulation is only just now being investigated.